Measuring health literacy among older inpatients after elective surgery: evaluation of the European Health Literacy Survey Questionnaire-short form (HLS-EU-Q16) - Moritz Sebastian Schönfeld; Julia Rinke; Cynthia Olotu; Claudia Langebrake; Levente Kriston; Rainer Kiefmann; Corinna Bergelt (Frontiers in Psychology, 2026)
Introduction Health literacy (HL) has been recognized as a central construct in healthcare that contributes to individual health and serves as a predictor of various health outcomes. Recently, vulnerable groups such as older adults have increasingly become the focus of studies examining HL. In this context, various questionnaires have been developed and deployed, including the widely used European Health Literacy Survey Questionnaire (HLS-EU-Q47) and its short form (HLS-EU-Q16). However, it remains unclear whether results from population- and community-based studies can be applied to specific inpatient populations. Furthermore, research focusing on HL among older patients is limited. The aim of this study was therefore to examine distributions of HL across different characteristics and its associations with other health variables and to assess the psychometric properties of the HLS-EU-Q16 in a sample of older inpatients after elective surgery. Methods We analyzed a cross-sectional sample of 143 hospital patients aged 65 years or older who underwent elective surgery at a university hospital in northern Germany. Levels of HL, along with various sociodemographic and health-related variables, were examined. Additionally, we conducted a confirmatory factor analysis (CFA) to examine the latent factor structure of the HLS-EU-Q16 in this context. Results The average age of patients was 73.2 years (SD = 5.8), with 52.4% being male. Nearly half (47.6%) of the sample had difficulties in handling health information (i.e., limited HL). Overall, 13.8, 33.8, 40.0, and 12.3% of patients were classified as having inadequate, problematic, sufficient, and excellent HL, respectively. Patients reported the greatest difficulties with items related to mental health and media on the HLS-EU-Q16. No significant differences in HL levels were observed between age groups, genders, or other sociodemographic variables ( p > 0.05). Regarding the CFA, we were unable to fully replicate the three-factor structure of the HLS-EU-Q16. Conclusion Our findings align with previous research indicating high rates of limited HL among older adults. However, we were unable to confirm the three-factor model of the HLS-EU-Q16, which adds to the mixed findings across different participant groups and contexts of previous studies. Developing or adapting HL questionnaires for clinical purposes may improve their relevance and usability in future studies.